Quantitative Classification of Uterine Myoma Perfusion on DCE-MRI: Retrospective Analysis of Data and Clinical Implications - Alan Bruszewski; Agnieszka Lach; Maciej Wilczak; Karolina Chmaj-Wierzchowska (Diagnostics)
Background/Objectives: The degree of vascularization of myomas plays an important role in both diagnosis and the selection of appropriate treatment. This is particularly relevant for minimally invasive therapies such as uterine artery embolization (UAE), high-intensity focused ultrasound (HIFU), or radiofrequency ablation (RFA) in uterine myomas, as their effectiveness is highest in well-vascularized lesions. This study aimed to analyze the perfusion of uterine myomas using dynamic contrast-enhanced magnetic resonance imaging and to develop a new quantitative classification of lesion vascularization, referencing the Funaki classification. Methods: The study included 56 female patients. Three parameters were determined for each lesion: the maximum signal enhancement (Ratio), time to peak, and mean signal intensity (Mean). A KMeans cluster analysis (k = 3) was performed, dividing the data into three groups corresponding to Funaki types I–III. Results: Significant differences were observed between the groups. Type III myomas were found only in older patients, which may be relevant when qualifying patients for vascularization-targeted therapies such as HIFU or radiofrequency ablation. Conclusions: The proposed classification may serve as a basis for automating the assessment of myomas and supporting clinical decision-making.